Влияние объекта педагогической деятельности на изменение профессионально-личностных характеристик учителя: деструктивный аспект - Zheldochenko, Liudmila D.; Rogov, Evgenii I. (Rossijskij psihologičeskij žurnal., 2016)
In the paper the focus of attention is on the features of changes in professional and personal characteristics of teachers of comprehensive schools and orphan asylums. In accordance with the author’s concept of professionalization, the article considers changes in professional and personal characteristics in three directions. The authors dene these three vectors as the following: psychological characteristics of the subject; features of professional activity; features of the object of activity and interaction with it. To identify various behaviors of subjects that have a negative impact on personality development in school teachers and teachers of orphan asylums the authors used the following standard methods: the test-questionnaire of self-attitude (V. V. Stolin), “Sense-of-Life orientations” test (D. A. Leontiev), “Job Satisfaction” test (V. A. Rozanova), technique for diagnostics of the level of emotional burnout (V.V.Boyko), Strategic Approach to Coping Scale (SS) by S. Hobfoll, technique of general communicative tolerance (V. V. Boyko), Bass-Darky questionnaire for estimating the level of aggression. The data obtained suggest that the teachers of orphan asylums had dierences in the destructive changes of personal and professional characteristics in comparison with school teachers. When explaining such dierences, the authors emphasize the very nature of professional activity of teachers of orphan asylums, their interactionwith apsychologically complicated object of labor. The destructive changes took place in all three dimensions of professionalization. The teachers of orphan asylums scored lower on measures of self-attitude and life sensemaking as psychological characteristics ofapersonal-sense component of the destructive changes in professional development. Psychological characteristics of an individual-activity component of the professional development of the teachers of orphan asylums manifested themselves in extreme dissatisfaction with their own work, its conditions, organization, opportunities for career growth, as well as in the nancial aspect. The ndings of the study also showed that the emotional burnout syndrome was more prominent in the teachers of orphan asylums; more often they behave antisocially in a stressful situation. The study demonstrated a communicative component of the destructive changes of the professional development of the teachers of orphan asylums in a high intolerance and prominent aggressive reactions (mainly verbal aggression). В работе исследуются особенности изменения профессионально-личностных характеристик педагогов общеобразовательных школ и социальных приютов. В соответствии с авторской концепцией профессионализации, изменение профессионально-личностных характеристик рассматривается в пространстве, образованном тремя векторами, обозначенными как психологические особенности субъекта, особенности самой профессиональной деятельности, особенности объекта деятельности и взаимодействия с ним. Для фиксации различных поведенческих проявлений субъектов, оказывающих негативное влияние на развитие личности в профессиональной деятельности педагогов школы и педагогов социального приюта использовались следующие стандартные методики: тест-опросник самоотношения В. В. Столина, тест «Смысложизненные ориентации» Д. А. Леонтьева, тест «Удовлетворенность работой» В. А. Розановой, методика диагностики уровня эмоционального выгорания В. В. Бойко, опросник SАСS – «Стратегии преодоления стрессовых ситуаций» С. Хобфолл, методика общей коммуникативной толерантности В. В. Бойко, тест на определение уровня агрессивности Басса–Дарки. Полученные результаты свидетельствуют о наличии различий в деструктивных изменениях профессионально-личностных характеристик педагогов социального приюта в сравнении с педагогами общеобразовательной школы, что обусловлено спецификой профессиональной деятельности педагогов приюта, взаимодействием с психологически сложным объектом труда. Деструктивные изменения протекают по всем трем направлениям профессионализации. Психологические особенности личностно-смыслового компонента деструктивных изменений профессионального развития педагогов социального приюта характеризуются более низкими, по сравнению с педагогами общеобразовательной школы, показателями самоотношения и осмысленности жизни. Психологические особенности индивидуально-деятельностного компонента деструктивных изменений профессионального развития педагогов приюта проявляются в демонстрации крайней неудовлетворенности своей работой, ее условиями, организацией, возможностью карьерного роста, а также финансовой составляющей, по сравнению с педагогами общеобразовательных школ. У педагогов социальных приютов более выражен синдром эмоционального выгорания: как показали результаты проведенного исследования, они чаще прибегают к асоциальным действиям в стрессовой ситуации. Коммуникативный компонент деструктивных изменений профессионального развития педагогов социальных приютов обнаруживается в более высокой интолерантности, более выраженных агрессивных реакциях, проявляющихся преимущественно через вербальную агрессию.